Runtime verification 9th international workshop, RV 2009, Grenoble, France, June 26-28, 2009 : selected papers - RV 2009 (Lecture notes in computer science, 2009)
Rule systems for runtime verification: a short tutorial -- Verification, testing and statistics -- Type-separated bytecode – its construction and evaluation -- Runtime verification of safety-progress properties -- Monitor circuits for LTL with bounded and unbounded future -- State joining and splitting for the symbolic execution of binaries -- The lime interface specification language and runtime monitoring tool -- A concurrency testing tool and its plug-ins for dynamic analysis and runtime healing -- Bridging the gap between algebraic specification and object-oriented generic programming -- Runtime verification of C memory safety -- A combined on-line/off-line framework for black-box fault diagnosis -- Hardware supported flexible monitoring: early results -- DMaC: distributed monitoring and checking.